A Qualitative Study on Integrating Language Development Methodology for Enhancing Early Childhood Creativity and Giftedness - Listyowati, Anies; Hartanti, Jahju; Merdika, Natasya (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
The preschool years represent a critical stage in children's cognitive, socio-emotional, linguistic, and psychomotor development, with creativity and giftedness as essential components of early education. However, the current education system lacks comprehensive strategies to effectively integrate language development as a foundational approach to nurturing creativity and talent. This study investigates the relationship between language development and the cultivation of creativity in preschool children through a qualitative methodology incorporating teacher interviews and classroom observations. Thematic analysis was employed to identify patterns in pedagogical practices that promote creativity through linguistic expression. The findings reveal that parental involvement and interactive learning methods foster children's creativity and gifted potential. The novelty of this study lies in its emphasis on linguistic expressions as indicators of cognitive and creative growth, addressing a gap in previous research that has largely overlooked the specific role of language in the development of giftedness during early childhood. These insights offer valuable contributions for educators in designing more effective strategies to enhance preschoolers’ creativity through language development.